Papel protetor do 2-feniletinil-butilterúrio em modelos de dano cognitivo em camundongos e na apoptose em células humanas - Souza, Ana Cristina Guerra de (2013)
Memory is considered to be a process that has several stages, including acquisition, consolidation and retrieval. Memory impairment occurs when important synapses are modified. Alzheimer s disease (DA) is the most common cause of dementia. DA is characterized by cognitive damage, accumulation of the pathogenic amyloid-β (Aβ) peptide, and cholinergic dysfunction. Moreover, oxidative stress is associated with DA. Therapies used for dementia are still palliative rather than curative. Consequently, new therapies are urgently required. Biological effects of tellurium compounds have been studied, leading to a set of interesting and promising applications. Accordingly, 2-phenylethinyl-butyltellurium (PEBT), an organotellurium compound, has been reported as antioxidant. The purpose of this study was to characterize PEBT as a promising alternative for memory improvement and prevention of cognitive deficits, using experimental models of DA in mice. Initially, the present study was conducted to evaluate the effect of a single oral administration (p.o.) of PEBT at a dose of 10 mg/kg on memory, employing the step-down inhibitory avoidance task. PEBT administered 1 h before training, immediately after training or 1 h before the test session of the step-down inhibitory avoidance task increased the step-down latency time in comparison to the control mice, improving acquisition, consolidation, and retrieval of memory, respectively. The glutamate uptake, but not glutamate release, by cerebral cortex and hippocampal slices of mice was inhibited after 1 h of treatment with PEBT. After 24 h of PEBT exposure, the inhibition of cerebral cortex glutamate uptake disappeared. The improvement of memory by PEBT seems most likely to be mediated through an interaction with the amino acid transporters of the glutamatergic system. Thereafter, a subchronic PEBT treatment (1 mg/kg, p.o., for 10 days) after injection of Aβ(25-35) (3 nmol/3 μl/per site, intracerebroventricular) reversed Aβ-induced learning and memory deficits in the Morris water maze and step-down inhibitory avoidance tasks. In addition, PEBT (10 mg/kg, p.o.), administered 30 min before scopolamine (1 mg/kg, intraperitoneal), ameliorated memory deficit induced by this amnesic agent in the Morris water maze. Further, scopolamine was given 30 min before training and test or immediately post-training of step-down inhibitory avoidance task, inducing damage on acquisition, retrieval, and consolidation of memory, respectively. PEBT, administered 30 min before scopolamine, improved consolidation and retrieval stages, but not acquisition. General locomotor and exploratory activities, evaluated in the open-field test, were similar in all mice. Finally, the antiapoptotic effect of PEBT was evaluated. Human retinal pigment epithelial cells (ARPE-19 cell line) were exposed to in vitro oxidative stress by 10 ng/ml tumor necrosis factor-α and 600 μM H2O2. One hour PEBT incubation at concentrations of 7.5 and 10 μM attenuated the apoptosis induced by oxidative stress. This effect lasted up to 6 hours after oxidative stress induction. PEBT (5 and 10 μM) inhibited oxidative stress-induced poly (ADP-ribose) polymerase (PARP) cleavage and restored extracellular-signal-related kinase (ERK) phosphorylation decreased by oxidative stress. The protective mechanism exerted by PEBT against oxidative stress may involve PARP cleavage, regulation of ERK pathway, as well as its known antioxidant properties. In conclusion, the finds of the present thesis point out the ameliorative effect of PEBT on memory stages (acquisition, consolidation and retrieval). Likewise, PEBT improved memory impairment in mice. These effects seem to be due to strengthen the physiological glutamatergic tonus by PEBT and the antiapoptotic effect of PEBT. Therefore, PEBT could be considered a candidate for the prevention of memory deficits such as those observed in DA.